The application of classification methods to the gross error detection problem - Gerber, E.; Auret, L.; Aldrich, Chris (International Federation of Automatic Control, 2014)
All process measurements are corrupted by the presence of measurement error to some degree.The attenuation of the measurement error, especially large gross errors, can increase the value of the process measurements. Gross error detection has typically been performed through rigorous statistical hypothesis testing. The assumptions required to derive the necessary statistical properties are restrictive, which lead to investigation of alternative approaches, such as artificial neural networks. This paper reports the results of an investigation into the utility of classification trees and linear and quadratic classification functions for resolving the gross error detection and identification problems.